Sliding member, method for producing same, and coating film
By providing carbon layered portions with columnar tissue on the sliding surface of the sliding member, the problem of sliding member coating is solved, which takes into account both the crack resistance, wear resistance and low friction, and achieves high productivity homogenization and Thick filming avoids defects and cracks.
Patent Information
- Application Number
- CN202380040628.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-22
- Filing Date
- 2023-09-22
- Publication Date
- 2025-01-03
AI Technical Summary
The existing sliding component coatings are difficult to take into account both the crack resistance, wear resistance and low friction, and defects and cracks are easily generated during the thick filming process, and the productivity is low.
A plurality of laminated parts are formed on the sliding surface of the sliding member, and a carbon layer with columnar tissue is provided between the laminated parts. The cross-section is displayed by the bright field TEM observation section, and the black hard carbon layer that is relatively black or black and relatively white or Repeating units of a white, white hard carbon layer with columnar structure to relieve stress and achieve homogenization and thick filmization.
A sliding member with excellent crack resistance, wear resistance and peel resistance is achieved, friction loss is reduced, and homogenization and thick film are achieved through high productivity, avoiding defects and cracks.
Smart Images

Figure CN119256175A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a sliding part, a method for manufacturing the same, and a coating film. Specifically, the present invention relates to a coating film that exhibits excellent chipping resistance and wear resistance and excellent peeling resistance (adhesion), can reduce friction, is particularly not prone to defects and cracks, and is homogenized and thickened, a sliding part having the coating film, and a method for manufacturing the sliding part. Background Art
[0002] In recent years, in various industrial fields, especially in the automotive field, research on hard carbon layers as surface coatings in sliding parts that require sliding properties, such as engine substrates and other mechanical substrates, has been conducted vigorously. Hard carbon layers are generally referred to by various names such as diamond-like carbon (DLC) layers, amorphous carbon layers, i-carbon layers, and diamond-like carbon layers. Such hard carbon layers are classified as amorphous in structure.
[0003] It is generally believed that the hard carbon layer is a mixture of single bonds found in diamond crystals and double bonds found in graphite crystals. In addition to the high hardness, high wear resistance, and excellent chemical stability of diamond crystals, the hard carbon layer also has low hardness, high lubricity, and excellent affinity with the other party like graphite crystals. In addition, since the hard carbon layer is amorphous, it has excellent flatness, low friction (i.e., small friction coefficient) when in direct contact with the other material, and excellent affinity with the other party.
[0004] For the sliding surface of a sliding part, chipping resistance (defect resistance) and wear resistance are important characteristics. However, the chipping resistance (defect resistance) and wear resistance are in a trade-off relationship, so it is difficult to provide a coating film that satisfies them. Therefore, as a means, research is being conducted to provide a hard carbon layer with low hardness or a mixed layer of hard carbon with low hardness and hard carbon with high hardness to achieve both chipping resistance and wear resistance.
[0005] However, the current situation is that it is still not fully achieved to achieve both chipping resistance and wear resistance. In particular, for the coating film provided on the sliding parts that are subjected to high loads, such as piston rings, in addition to chipping resistance and wear resistance, low friction and peeling resistance are required, but the improvement of these characteristics is still insufficient. In recent years, various technologies have been proposed to solve such technical problems.
[0006] For example, Patent Document 1 proposes a technique for forming a hard carbon layer with excellent durability by a PVD method, achieving both chipping resistance and wear resistance of the hard carbon layer after film formation, and improving low friction and peeling resistance. This technique is a coating film coated on the surface of a substrate, wherein when a cross section is observed using a bright field TEM image, a white hard carbon layer that appears relatively white and a black hard carbon layer that appears black are alternately stacked in the thickness direction, and the total film thickness exceeds 1 μm and is less than 50 μm, and the white hard carbon layer has a region that grows in a fan-shaped manner in the thickness direction.
[0007] In addition, Patent Document 2 proposes a sliding component having a coating film that exhibits constant and stable chipping resistance and wear resistance and excellent peeling resistance (adhesion), and the coating film. This technology is a sliding component having a coating film composed of a hard carbon layer on a sliding surface, wherein the coating film has a thickness in the range of 1 μm to 50 μm when a cross section is observed using a bright field TEM image, and a repeated unit including a black hard carbon layer that is relatively black and a white hard carbon layer that is relatively white is stacked in the thickness direction, and the coating film has an inclined region and a homogeneous region, wherein the inclined region is provided on the substrate side and the thickness of the white hard carbon layer in the repeated unit gradually increases in the thickness direction, and the homogeneous region is provided on the surface side and the thickness of the white hard carbon layer in the repeated unit is the same or substantially the same in the thickness direction, wherein the inclined region has a V-shaped or radially growing morphology in the thickness direction, and the homogeneous region does not have a V-shaped or radially growing morphology in the thickness direction.
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent document 1: WO2017 / 104822A1
[0011] Patent Document 2: WO2018 / 235750A1 Summary of the invention
[0012] Technical problem to be solved by the invention
[0013] The coating film of the sliding part is required to have chipping resistance, wear resistance, low friction, etc., and further reduction of friction (friction loss) is expected. The hard carbon layer constituting the coating film is expected to be a material capable of achieving low friction.
[0014] For the coating film, the hard carbon layer is required to be thicker so that the wear resistance and other characteristics can be continuously exerted for a long period of time. However, if the laminated portion formed by repeated unit lamination including the black hard carbon layer and the white hard carbon layer is simply thickened, stress (synonymous with deformation) is easily accumulated in the laminated portion, and defects and cracks are easily generated in the coating film due to the accumulated stress. In addition, even if a thick coating film is obtained, if the film quality at each part in the thickness direction is different, the characteristics at each part will change, and the wear resistance and other characteristics may no longer be stable over time. In addition, even if a thick coating film is formed, it is meaningless if the method is inferior in productivity.
[0015] The present invention is made to solve the above-mentioned technical problems, and its purpose is to provide a new sliding component, a manufacturing method thereof, and a coating film that exhibits excellent chipping resistance and wear resistance and peeling resistance (close adhesion), can reduce friction, is particularly not prone to defects and cracks, and achieves homogenization and thick film with high productivity.
[0016] Technical solutions for solving technical problems
[0017] (1) The sliding component according to the present invention is a sliding component having a coating film on a sliding surface of a substrate, characterized in that the coating film has a plurality of laminated parts and a carbon layer provided between each of the laminated parts, and that when the laminated part is observed in a cross section using a bright field TEM image, repeated units of a hard carbon layer that is relatively black or blackish and a hard carbon layer that is relatively white or whiteish are laminated in a thickness direction, and the carbon layer has a columnar structure.
[0018] According to the invention, the stress (deformation) that is easily accumulated in the laminated part when only the laminated part is thickened can be alleviated by providing a carbon layer with a columnar structure between each laminated part. As a result, it is possible to provide a sliding part that does not produce defects or cracks in the coating film even if the laminated part is thickened. In a sliding part with such a structural form, the cross-sectional form of each laminated part appearing in the thickness direction of the coating film is homogeneous, so it can be considered that the characteristics in the thickness direction are also homogeneous, and both homogenization and thickening of the film can be achieved with high productivity. It should be noted that the columnar structure refers to a structure that extends in the thickness direction in a relatively black or off-white columnar form in a relatively white or off-white carbon layer.
[0019] In the sliding part according to the present invention, the thickness of the laminated portion is in the range of 2 to 9 μm, and the thickness of the coating film is in the range of 4 to 40 μm. According to the present invention, the thickness of the laminated portion can be thickened within the above range, and the laminated portion can be further laminated via a carbon layer so that the total thickness of the coating film is within the above range without defects or cracks in the coating film. It should be noted that in order to repeatedly laminate laminated portions with a thickness of 2 to 9 μm via a carbon layer to form a coating film with a thickness of 4 to 40 μm, the coating film with the above thickness range can be formed by making the number of laminated portions with a thickness of 2 to 9 μm within the range of about 2 to 10.
[0020] In the sliding part involved in the present invention, the carbon layer is formed in sequence with a black carbon layer that is relatively black or off-black and a white carbon layer that is relatively white or off-white, and the relatively black columnar structure is present in the white carbon layer. The carbon layer is obtained by pausing film formation for a certain period of time after forming a laminated portion of a specified thickness, and forming a film under specified conditions after reaching a relatively low temperature. In such a carbon layer, the black carbon layer is produced in the initial stage of film formation, and the white carbon layer is produced thereafter. The columnar structure is present in the white carbon layer. By arranging a carbon layer of such a form between each laminated portion, the stress of the laminated portion is relieved, and it can become a coating film that is not prone to defects and cracks. It should be noted that the white carbon layer and the columnar structure appearing therein can be considered as a low-density structure, and therefore it can be considered to have an effect on stress relief of the laminated portion.
[0021] In the sliding component of the present invention, the black hard carbon layer has a thickness of 2 / (sp 2 +sp 3 )] ratio is in the range of 0.05 to 0.75, and the white hard carbon layer has a [sp 2 / (sp 2 +sp 3 )] is greater than the [sp 2 / (sp 2 +sp 3 )] ratio and is in the range of 0.20 to 0.80, the white carbon layer in the carbon layer has a [sp 2 / (sp 2 +sp 3 )] ratio is in the range of 0.20 to 0.80.
[0022] In the sliding component according to the present invention, an initial carbon layer is formed as a lower layer before the coating film is formed.
[0023] In the sliding component according to the present invention, in the laminated portion, an inner-laminated-portion carbon layer is formed on the white hard carbon layer as a lower layer of the black hard carbon layer.
[0024] The sliding component according to the present invention has a surface layer portion as an outermost layer on the laminated portion, and the thickness of the surface layer portion is 0.1 to 10 μm.
[0025] In the sliding component according to the present invention, the sliding component is a piston ring.
[0026] (2) The coating film according to the present invention is characterized in that it has a plurality of laminated parts and a carbon layer provided between each of the laminated parts, wherein the laminated parts have repeated units of a relatively black or blackish hard carbon layer and a relatively white or whiteish hard carbon layer laminated in the thickness direction when a cross section is observed using a bright field TEM image, and the carbon layer has a columnar structure.
[0027] In the coating film according to the present invention, the thickness of the laminated portion is in the range of 2 to 9 μm, and the thickness of the coating film is in the range of 4 to 40 μm.
[0028] In the coating film according to the present invention, the carbon layer includes a black carbon layer showing relatively black or blackish color and a white carbon layer showing relatively white or whiteish color in sequence, and the relatively black columnar structure exists in the white carbon layer.
[0029] In the coating film according to the present invention, an initial carbon layer is formed as a lower layer before the coating film is formed.
[0030] In the coating film according to the present invention, in the laminated portion, an intra-laminated portion carbon layer is formed on the white hard carbon layer as a lower layer of the black hard carbon layer.
[0031] The coating film according to the present invention has a surface layer portion as an outermost layer on the laminated portion, and the thickness of the surface layer portion is 0.1 to 10 μm.
[0032] (3) The method for manufacturing a sliding component according to the present invention is a method for manufacturing a sliding component according to any one of claims 1 to 5, wherein the sliding surface of the substrate has a coating film, the coating film having a plurality of laminated portions and a carbon layer provided between the laminated portions, wherein the laminated portion has a repeated unit of a relatively black or blackish hard carbon layer and a relatively white or whiteish hard carbon layer laminated in a thickness direction when a cross section is observed using a bright field TEM image, and the carbon layer has a columnar structure.
[0033] The carbon layer is obtained by forming the laminated portion to a predetermined thickness, pausing the film formation for a predetermined period of time, and then forming the film under predetermined conditions after the temperature reaches a relatively low level.
[0034] Effects of the Invention
[0035] According to the present invention, it is possible to provide a new sliding component, a manufacturing method thereof, and a coating film that exhibits excellent chipping resistance and wear resistance and peeling resistance (adhesion), can reduce friction, is particularly less prone to defects and cracks, and achieves homogenization and thick film with high productivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is a schematic cross-sectional view showing an example of the sliding component according to the present invention.
[0037] Figure 2 It is a schematic enlarged cross-sectional view showing an example of a coating film.
[0038] Figure 3 This is a bright-field TEM image showing a cross section of an example of a coating film.
[0039] Figure 4 This is a bright-field TEM image of an enlarged cross section of a laminated portion constituting the coating film.
[0040] Figure 5 This is a bright-field TEM image of an enlarged cross section of a carbon layer constituting the coating film.
[0041] Figure 6 This is a bright-field TEM image showing a cross section of an example of the surface layer portion constituting the coating film.
[0042] Figure 7 This is a bright-field TEM image of an enlarged cross section of the surface layer.
[0043] Figure 8 This is a schematic cross-sectional view showing an example of a piston ring according to the present invention.
[0044] Fig. 9 This is a schematic diagram of the friction and wear test method performed using an SRV testing machine. DETAILED DESCRIPTION
[0045] The sliding member, the manufacturing method thereof, and the coating film according to the present invention will be described in detail with reference to the accompanying drawings. It should be noted that the present invention is not limited to the following description and the accompanying drawings, and also includes modifications within the scope of the gist thereof.
[0046] [Sliding parts]
[0047] The sliding component 10 according to the present invention is, for example, Figure 8As shown in the example of the piston ring, the sliding surface 16 on the substrate 11 has a coating 1. The coating 1 is characterized in that it has a plurality of laminated parts 3 and a carbon layer 4 provided between the laminated parts 3, and in the laminated parts 3, when a cross section is observed using a bright field TEM image, a repeated unit 2 of a hard carbon layer B showing a relatively black or blackish black and a hard carbon layer W showing a relatively white or whiteish white is laminated in the thickness direction Y, and the carbon layer 4 has a columnar structure 4c.
[0048] In this sliding component 10, the stress (deformation) that is likely to accumulate in the laminated portion 3 when the laminated portion 3 is simply thickened can be alleviated by providing a carbon layer 4 having a columnar structure 4c between each laminated portion 3. As a result, even if the laminated portion 3 is thickened, it is not easy to produce defects or cracks in the coating film 1. In the sliding component 10 with such a structural form, the cross-sectional form of each laminated portion 3 appearing in the thickness direction Y of the coating film 1 is homogeneous, so it can be considered that the characteristics in the thickness direction Y are also homogeneous, and both homogenization and thickening can be achieved with high productivity. It should be noted that the columnar structure 4c refers to a structure that extends in the thickness direction Y in a relatively black or off-white columnar form in the white carbon layer 4b that appears relatively white or off-white.
[0049] The bright field TEM image can be obtained by observing the coating film 1 thinned by using FIB (Focused Ion Beam) with a TEM (Transmission Electron Microscope) at an accelerating voltage of 300 kV, for example. The thickness direction Y refers to the direction in which the laminated portion 3 is repeatedly laminated on the substrate 11 with the carbon layer 4 interposed therebetween. When observing with the bright field TEM image, in the present application, "relatively white or off-white" is sometimes referred to as "white", and "relatively black or off-black" is sometimes referred to as "black".
[0050] The components of the sliding component 10 are described in detail below. It should be noted that, in the following, the sliding component 10 is mostly described by taking a piston ring (also indicated by the reference numeral 10) as an example, but the sliding component 10 of the present invention is not limited to a piston ring. 2 / (sp 2 +sp 3 )] is simplified and expressed as "sp 2 / sp 3 Compare".
[0051] (Base material)
[0052] like Figure 1As shown, the substrate 11 is a target part provided with the coating film 1. The substrate 11 is not particularly limited, and examples thereof include iron-based metals, non-iron-based metals, ceramics, hard composite materials, etc. For example, examples thereof include carbon steel, alloy steel, hardened steel, high-speed tool steel, cast iron, aluminum alloy, magnesium alloy, and superhard alloy. It should be noted that, considering the film forming temperature of the coating film 1, it is preferred to use a substrate whose characteristics do not significantly deteriorate at a temperature exceeding 200°C.
[0053] As the substrate 11 when the coating film 1 is applied to the piston ring 10, various substrates used as the substrate of the piston ring 10 can be cited, without particular limitation. For example, various steel materials, stainless steel materials, casting materials, cast steel materials, etc. can be applied. Among them, martensitic stainless steel, chrome-manganese steel (SUP9 material), chrome-vanadium steel (SUP10 material), silicon-chrome steel (SWOSC-V material), etc. can be cited. The substrate 11 can have Figure 1 The base layer 12 is shown.
[0054] The substrate 11 may be pre-treated as needed. As a pre-treatment, it is preferred to perform surface grinding to adjust the surface roughness. The surface roughness is preferably adjusted by, for example, polishing the surface of the substrate 11 with diamond abrasive grains to perform surface grinding. For such a substrate 11, it can be preferably applied as a pre-treatment before forming the intermediate layer 13 described later or as a pre-treatment of the base layer 12 pre-set before forming the intermediate layer 13.
[0055] (basal layer)
[0056] The base layer 12 is provided on the substrate 11 as required. As the base layer 12, a layer for improving the adhesion with the intermediate layer 13 described later can be cited, and it is not particularly limited. Specifically, for the base layer 12, a compound layer such as a nitride, carbonitride or carbide of at least one of Cr, Ti, Si, Al, etc. can be cited, and specifically, CrN, CrBN, TiN, CrAlN, TiC, TiCN, TiAlSiN, etc. can be cited. For the base layer 12, for example, the base material 11 can be set in a chamber, and after the chamber is made vacuum, preheating, ion cleaning, etc. are performed to introduce inert gas, nitrogen, etc., and the base layer 12 is formed by means of vacuum evaporation method, ion plating method, etc. In addition, it can also be a nitrided layer formed by nitriding treatment (not shown). It should be noted that the piston ring 10 has a coating film 1 that exhibits excellent wear resistance even without a compound layer or a nitrided layer, so the base layer 12 is not an essential component.
[0057] (Middle layer)
[0058] like Figure 1As shown, the intermediate layer 13 is preferably provided between the substrate 11 (the base layer 12 if the base layer 12 is provided) and the coating film 1 as required. The intermediate layer 13 can further improve the adhesion between the substrate 11 (base layer 12) and the coating film 1. As the intermediate layer 13, a layer having at least one or two or more elements such as Cr, Ti, Si, W, and B can be cited.
[0059] As the intermediate layer 13, titanium film or chromium film can be cited. The intermediate layer 13 may not be provided and is arbitrary. The intermediate layer 13 such as titanium film or chromium film can be formed by various film forming means such as vacuum evaporation, sputtering, ion plating, etc. For example, the substrate 11 can be set in a chamber, and after the chamber is made vacuum, preheating, ion cleaning, etc. are performed and an inert gas is introduced to form the intermediate layer 13. The thickness of the intermediate layer 13 is not particularly limited, and is preferably in the range of 0.05 μm to 2 μm. It should be noted that the intermediate layer 13 is preferably formed at least on the peripheral sliding surface 16 where the piston ring 10 contacts and slides with the cylinder liner (not shown), but can also be formed on other surfaces, such as the upper surface, lower surface, and inner peripheral surface of the piston ring 10.
[0060] The intermediate layer 13 can be formed directly on the substrate 11 or on the base layer 12. The intermediate layer 13 can improve the adhesion between the substrate 11 (base layer 12) and the coating film 1. It should be noted that, between the intermediate layer 13 and the coating film 1, in order to further improve their adhesion, other layers can also be provided as needed. For example, a film having the same or substantially the same composition as the coating film 1 described later can be formed as a hard carbon base film.
[0061] (Initial carbon layer)
[0062] like Figure 1 As shown, it is more preferred that the initial carbon layer 14 is provided on the substrate 11 before the coating film is formed, or formed on the base layer 12 when the base layer 12 is provided, or formed on the intermediate layer 13 when the intermediate layer 13 is further provided. It should be noted that in the experimental examples described later, the initial carbon layer 14 is provided on the intermediate layer 13.
[0063] The film forming conditions of the initial carbon layer 14 are not particularly limited, and the film can be formed by the film forming treatment (bombardment treatment based on arc ion plating) described in the experimental example described later. Bombardment treatment is a treatment using a carbon target, and it is expected that the adhesion of the coating film 1 will be improved, so it is preferably applied in the present invention. The film forming conditions in this experimental example are just one example, and the bias voltage, arc current, treatment start temperature, and treatment time can be set arbitrarily. The bias voltage of the initial carbon layer 14 is not particularly limited, but is preferably in the range of -600 to -1000V. In the embodiment described later, as an example of the conditions of the bombardment treatment, the film is formed before the formation of the coating film 1 with a bias voltage of -750V, an arc current of about 40A, and a prescribed time until the thickness becomes about 0.2μm. The thickness of the initial carbon layer 14 is not particularly limited, but is preferably in the range of 0.05μm or more and 0.5μm or less.
[0064] (Coating film)
[0065] like Figure 1 and Figure 2 As shown, the coating film 1 has a plurality of laminated parts 3 and a carbon layer 4 provided between the laminated parts 3. The laminated part 3 has two kinds of hard carbon layers (reference numerals W and reference numerals B) that are relatively white and black when observing a bright field TEM image of the cross section thereof. The black hard carbon layer B and the white hard carbon layer W are laminated to form a repetitive unit 2, and the repetitive unit 2 is laminated in the thickness direction Y to form the laminated part 3. It should be noted that, although it has been explained, "relatively" refers to the relative relationship of the color tone when observing the cross section using a bright field TEM image, and the layer that appears black or blackish is the "black hard carbon layer B", and the layer that appears white or whiteish is the "white hard carbon layer W".
[0066] When the coating film 1 is applied to the piston ring 10, as Figure 6 As shown, the coating 1 is formed at least on the outer peripheral sliding surface 16 of the piston ring 10 that slides against the cylinder liner (not shown). It should be noted that the coating 1 may be formed on any other surface, such as the upper surface, lower surface, or inner peripheral surface of the piston ring 10.
[0067] (Lamination section)
[0068] like Figure 1 , Figure 2 as well as Figure 3 As shown in FIG. 1 , the laminated portion 3 is formed by laminating a repeated unit 2 of a black hard carbon layer B and a white hard carbon layer W. The lamination order of the black hard carbon layer B and the white hard carbon layer W is not particularly limited. Figure 1 and Figure 2In the example of , a black hard carbon layer B is formed and a white hard carbon layer W is formed thereon to form a stack of repetitive units 2, but the opposite form may be used, that is, a white hard carbon layer W is formed and a black hard carbon layer B is formed thereon to form a stack of repetitive units 2. The black hard carbon layer B and the white hard carbon layer W constituting the repetitive unit 2 are formed adjacent to each other.
[0069] The relatively black hard carbon layer B has the same high density as the prior art, sp 2 / sp 3 Smaller than the white hard carbon layer, excellent strength, low density, sp 2 / sp 3 The ratio is large, and the low friction and chipping resistance are excellent. However, the laminated portion 3 constituting the coating film 1 according to the present invention has a different hardness level compared with the prior art. Among the adjacent black hard carbon layer B and white hard carbon layer W, the white hard carbon layer W has a higher hardness than the black hard carbon layer B. That is, the black hard carbon layer B has a lower hardness and a higher density than the adjacent white hard carbon layer W. Conversely, the white hard carbon layer W has a higher hardness and a lower density than the adjacent black hard carbon layer B.
[0070] For sp 2 / sp 3 For example, the white hard carbon layer W is larger than the black hard carbon layer B. Therefore, in more detail, the black hard carbon layer B is lower in hardness than the adjacent white hard carbon layer W. 2 / sp 3 The white hard carbon layer W has a higher hardness than the adjacent black hard carbon layer B. 2 / sp 3 The laminated portion 3 formed by the repeated units 2 of the black hard carbon layer B and the white hard carbon layer W can form a sliding part 10 with excellent chipping resistance, wear resistance and peeling resistance (adhesion) based on the lamination effect of the hard carbon layers B and W with different properties, as shown in the results of the experimental example. It should be noted that sp 2 / sp 3 than [sp 2 / (sp 2 +sp 3 )] is simplified by the following “sp 2 / sp 3 The ratio is measured by the method described in the explanation column of "ratio".
[0071] Regarding hardness, the Vickers hardness of the black hard carbon layer B is preferably within the range of 700 to 1600 HV, more preferably within the range of 750 to 1200 HV. The Vickers hardness of the white hard carbon layer W is preferably higher than the Vickers hardness of the adjacent black hard carbon layer B and within the range of 1200 to 2200 HV, more preferably within the range of 1250 to 1900 HV.
[0072] About sp 2 / sp 3 Compared with the black hard carbon layer B, the sp 2 / sp 3 The ratio is preferably in the range of 0.05 to 0.75. 2 / sp 3 The ratio is preferably greater than the sp 2 / sp 3 ratio and is in the range of 0.20 to 0.80. 2 / sp 3 Compared with the small black hard carbon layer B, due to the carbon chain represented by diamond (sp 3 Chains) are relatively more, so the density is high, and thus the hardness is high, but in the present invention, although the density is high, the hardness is low. On the other hand, for sp 2 / sp 3 Compared with the large white hard carbon layer W, due to the carbon chain represented by graphite (sp 2 The density is low, and thus the hardness is low. In the present invention, although the density is low, the hardness is high. This is believed to be caused by the film forming process described later. It should be noted that sp 2 / sp 3 It can be measured by combining a transmission electron microscope (TEM) with an electron energy loss spectroscopy (EELS) TEM-EELS. It should be noted that "high", "low", "large" and "small" here refer to the relative height and size between the black hard carbon layer B and the white hard carbon layer W.
[0073] like Figure 4 As shown, the black hard carbon layer B has a mesh or fan-shaped structure in all or part of it. "Part" refers to the part on the surface side of the black hard carbon layer B, which may have a slightly mesh or fan-shaped structure, or may have a three-dimensional growth form that can be described as a mesh or fan. In this growth form, white hard carbon is sometimes included in the black hard carbon layer B. In addition, the triangular wave shape of the black hard carbon layer B can also be viewed as a V shape (a shape that gradually expands from the position of the fan axis) or a radial shape relative to the growth direction of the film.
[0074] like Figure 4As shown, a fine stripe pattern can be seen in the white hard carbon layer W, and a fine mesh pattern can be seen in the black hard carbon layer B. The reason why such a stripe pattern can be seen in the repeated layers (white hard carbon layer W, black hard carbon layer B) is considered to be due to the following reason: when the laminated portion 3 is formed on the sliding surface of the annular piston ring, the distance from the target continuously changes when the film is formed by rotation.
[0075] The laminated portion 3 can be formed by alternately performing film formation at a film formation temperature (substrate temperature) of, for example, 200° C. or less and film formation at a temperature exceeding 200° C. as the film formation temperature (substrate temperature) in the PVD method. 2 / sp 3 The white hard carbon layer W is slightly larger than that. On the other hand, the film formed at a temperature exceeding 200°C becomes sp 2 / sp 3 The black hard carbon layer B is smaller than the W. The laminated portion 3 can be formed by alternately laminating these films (W, B).
[0076] It should be noted that, in a part of the laminated portion 3, a bulge (not shown) may also appear between at least two or more layers (W, B) that are laminated. The bulge is a portion that can be seen as a bulge in the base layer, and can be seen as either a particle or a balloon. The laminated state with the presence of the bulge is not laminated in the same manner as arranged in the thickness direction Y, and is likely to appear mainly in the upper half, which looks like a disordered shape, but does not affect the properties such as wear resistance and crack resistance. For the formation of the bulge, it can be considered that the large particles during film formation become the starting point.
[0077] In the black hard carbon layer B and the white hard carbon layer W constituting the laminated portion 3, hydrogen is hardly contained based on the film forming conditions. If the hydrogen content is to be expressed, it can be 0.01 atomic % or more and less than 5 atomic %. The hydrogen content can be measured by HFS (Hydrogen Forward Scattering Spectrometry) analysis, and the rest is preferably substantially composed of carbon and does not contain N, B, Si and other inevitable impurities.
[0078] In the laminated part, such as Figure 4As can be seen in the figure, a thin carbon layer 15 (also referred to as a carbon layer 15 inside the laminated portion) is formed on the white hard carbon layer W as a lower layer of the black hard carbon layer B. The thin carbon layer 15 is a carbon layer that appears white or off-white, and is different from the carbon layer 4 (carbon layer 4 between laminated portions) and the initial carbon layer 14. The thin carbon layer 15 is formed as a lower layer of the black hard carbon layer B when the laminated portion 3 is formed by repeatedly forming the black hard carbon layer B and the white hard carbon layer W. The thickness of the thin carbon layer 15 is formed, for example, in the range of about 0.01 to 0.1 μm. In addition, a thin carbon layer (carbon layer inside the laminated portion) 15 may be formed on the black hard carbon layer B as a lower layer of the white hard carbon layer W.
[0079] (thickness)
[0080] Regarding the thickness ratio (TB / TW), the ratio (TB / TW) of the thickness TB of the adjacent black hard carbon layer B to the thickness TW of the white hard carbon layer W is preferably in the range of 1 / 10 to 1.5 / 1, and more preferably in the range of 1 / 10 to 1 / 1. Since the thickness ratio (TB / TW) of the repetitive unit 2 is within the above range, the thickness ratio can be arbitrarily controlled to be constant or variable in the thickness direction Y of the laminated portion 3. The change in the thickness ratio can be a gradual increase or decrease, or the thickness ratio at the beginning and end of film formation can be different from that of other parts. From the viewpoint of achieving both homogenization and thick film with high productivity, the thickness ratio is preferably constant in the thickness direction Y.
[0081] When the thickness ratio (TB / TW) of the black hard carbon layer B and the white hard carbon layer W is made the same in the thickness direction Y of the laminated portion 3, the low friction and chipping resistance of each repetitive unit 2 are made the same in each portion in the thickness direction Y. Therefore, even when the wear of the laminated portion 3 gradually progresses, the chipping resistance and wear resistance are in a stable state in each portion in the thickness direction, which is preferable. In addition, for example, when the thickness ratio (TB / TW) of the black hard carbon layer B and the white hard carbon layer W is gradually changed in the thickness direction Y of the laminated portion 3, the low friction and chipping resistance of the repetitive unit 2 in the initial sliding stage and the low friction and chipping resistance of the repetitive unit 2 after the initial sliding stage can be intentionally changed, so that the chipping resistance and wear resistance when the wear of the laminated portion 3 gradually progresses can be controlled.
[0082] Regarding the thickness T, the thickness T2 of the repetitive unit 2 is preferably within the range of 0.2 to 2 μm. The thickness T2 of each repetitive unit 2 can be arbitrarily controlled to be within the above range, but from the viewpoint of achieving both homogenization and thickening in the thickness direction Y with high productivity, the thickness T2 of the repetitive unit 2 is preferably constant in the thickness direction Y. The thickness T3 of the laminated portion 3 is preferably within the range of 2 to 9 μm. Regarding the thickness T3 of the laminated portion 3, it can also be arbitrarily controlled in the thickness direction Y to be within the above range, but from the viewpoint of achieving both homogenization and thickening in the thickness direction Y with high productivity, the thickness T3 of the laminated portion 3 is preferably constant in the thickness direction Y. It should be noted that from the viewpoint of thickening the coating film 1, the thickness T1 of the coating film 1 is preferably within the range of 4 to 40 μm. In order to make the thickness T1 of the coating film 1 4 to 40 μm, it is preferred that the number of laminated portions 3 with a thickness T3 of 2 to 9 μm be within the range of about 2 to 10. By setting the number of the laminated parts 3 to be within this range, the coating film 1 having the thickness within the above-mentioned range can be formed.
[0083] (Carbon layer)
[0084] like Figure 1 and Figure 2 As shown in FIG. 1 , the carbon layer 4 is disposed between the stacked portions 3 (between the stacked portions 3 and the stacked portions 3 ), and can also be referred to as an inter-stacked portion carbon layer. Figure 3 and Figure 5 As shown in FIG. 1 , the carbon layer 4 has a columnar structure 4c. By providing such a carbon layer 4 between each laminated portion 3, the stress (deformation) that is easily accumulated in the laminated portion 3 when the laminated portion 3 is simply thickened can be relieved. As a result, it is possible to form a sliding component 10 in which defects and cracks are not easily generated in the coating film 1 even if the laminated portion 3 is thickened. The sliding component 10 with such a structural form, such as Figure 3 and Figure 4 As shown, the cross-sectional morphology of each laminated portion 3 appearing in the thickness direction Y of the coating film 1 is homogeneous, so it can be considered that the characteristics in the thickness direction Y are also homogeneous, and both homogenization and thick film can be achieved with high productivity. It should be noted that the columnar structure 4c refers to a structure that extends in the thickness direction in a relatively white or off-white layer (white carbon layer 4b) in a relatively black or off-black columnar shape.
[0085] Regarding the carbon layer 4, in more detail, Figure 5As shown, a black carbon layer 4a that is relatively black or off-black and a white carbon layer 4b that is relatively white or off-white are formed in sequence, and a relatively black or off-black columnar structure 4c exists in the white carbon layer 4b. The carbon layer 4 is formed in the following manner: after forming a laminated portion 3 of a specified thickness, the film formation is temporarily stopped for a certain period of time, and the film is formed under specified conditions after reaching a lower temperature. In such a carbon layer 4, the black carbon layer 4a is generated in the initial stage of film formation, and the white carbon layer 4b is generated thereafter. The columnar structure 4c is generated in the carbon layer 4b during the formation process of the white carbon layer 4b. By arranging the carbon layer 4 of such a morphology between each laminated portion 3, the stress of the laminated portion 3 is relieved, and a coating 1 that is not prone to defects and cracks can be formed. It should be noted that the white carbon layer 4b and the columnar structure 4c appearing therein can be considered as a low-density structure, and therefore can be considered to have an effect on relieving the stress of the laminated portion 3. The white carbon layer 4b in such a carbon layer 4 has a [sp 2 / (sp 2 +sp 3 )] ratio is in the range of 0.20 to 0.80.
[0086] The thickness T4 of the carbon layer 4 is not particularly limited, but is selected to be within the range of 0.05 to 0.5 μm. By being within this range, the stress accumulated in the laminated portion 3 can be relieved, and it is possible to form a sliding component 10 in which defects and cracks are not easily generated in the coating film 1 even if the laminated portion 3 is thickened. If the thickness of the carbon layer 4 is less than 0.05 μm, the stress accumulated in the laminated portion 3 cannot be fully relieved, and defects and cracks are easily generated in the coating film 1 when the laminated portion 3 is thickened. On the other hand, when the thickness of the carbon layer 4 exceeds 0.5 μm, the stress accumulated in the laminated portion 3 can be relieved, but a thickness of 0.5 μm is sufficient for stress relief, and forming the carbon layer 4 in excess of 0.5 μm will result in a longer film formation time and poorer productivity. Therefore, the upper limit of the above-mentioned thickness T4 is specified from the perspective of productivity.
[0087] Comparing the thickness T4a of the black carbon layer 4a and the thickness T4b of the white carbon layer 4b constituting the carbon layer 4, Figure 5 In the example of , the example in which the white carbon layer 4b is thicker is shown, but the thickness T4a of the black carbon layer 4a and the thickness T4b of the white carbon layer 4b can be set to any thickness as long as they are within the range of the thickness T4 of the above-mentioned carbon layer 4. The thickness T4a of the black carbon layer 4a is not particularly limited, but can be set within the range of 0.01 to 0.34 μm, and the thickness T4b of the white carbon layer 4b is also not particularly limited, but can be set within the range of 0.016 to 0.4 μm.
[0088] As described above, the carbon layer 4 is formed after the film formation is temporarily stopped for a certain period of time and the temperature is relatively low. Therefore, the black carbon layer 4a appears by the film formation at the low temperature stage, and the white carbon layer 4b appears by the film formation at the stage after the temperature is gradually increased. The thickness ratio (T4a: T4b) of the thickness T4a of the black carbon layer 4a and the thickness T4b of the white carbon layer 4b is affected by the film formation time and film formation conditions of the carbon layer 4. When the film formation time of the carbon layer 4 is short and the film formation speed is slow (the bias voltage and arc current are low), the film formation temperature is not easy to rise and the black carbon layer 4a is easy to form. Therefore, the thickness ratio (T4a: T4b) is within the range of 2:1 to 1:2. On the other hand, when the film formation time of the carbon layer 4 is long and the film formation speed is fast (the bias voltage and arc current are relatively high), the film formation temperature is easy to rise and the white carbon layer 4b is easy to form. Therefore, the thickness ratio (T4a: T4b) is within the range of 1:1 to 1:4. exist Figure 5 In the example of FIG. 4 , it can be seen that the thickness T4 of the carbon layer 4 is approximately 0.19 μm, and the thickness ratio (T4a: T4b) is approximately 1:1.9.
[0089] The columnar structure 4c is generated in the white carbon layer 4b. The generation mechanism of the columnar structure 4c is not clear at present, but it appears in the white carbon layer 4b at the stage after the temperature gradually rises during the film formation of the carbon layer 4. The columnar structure 4c is a structure in which relatively black or blackish columnar longitudinal ribs extend in the thickness direction in the white carbon layer 4b. The present invention is characterized in that the white carbon layer 4b having the columnar structure 4c is arranged between the stacked parts 3, and the effect of the present invention can be achieved through such a carbon layer 4.
[0090] (Surface)
[0091] The surface layer 5 is not a necessary structure of the coating film 1, but Figure 1 As shown in FIG. 1 , it is preferably provided as the outermost layer on the laminated portion 3. The surface portion 5 is the same as the white hard carbon layer W of the laminated portion 3, and is composed of a relatively white hard carbon layer when a cross section is observed using a bright field TEM image. For the white hard carbon layer constituting the surface portion 5, since the carbon chain (sp 2 Chains) are relatively more, so the density is low, and thus the hardness is low. Such a surface portion 5 is formed by making the film forming temperature higher than the film forming temperature of each hard carbon layer (B, W) constituting the laminated portion 3. The thickness of the surface portion 5 is preferably in the range of 0.1 to 10 μm. By making the thickness of the surface portion 5 thinner than 0.1 μm and less than 1.0 μm, it can have the effect of reducing the friction when contacting with the other part in the initial stage of sliding. In addition, by making the thickness of the surface portion 5 thicker than 1 to 10 μm, it can have the effect of acting as an affinity layer with the other part and preventing damage to the aluminum cylinder bore.
[0092] The sp 2 / sp 3 The ratio is in the range of 0.20 to 0.80, preferably in the range of 0.30 to 0.60. 2 / sp 3 In comparison, when the black hard carbon layer B, the white hard carbon layer W, and the surface layer 5 constituting the laminated portion 3 are compared, [black hard carbon layer B<white hard carbon layer W≤surface layer 5] or [black hard carbon layer B<surface layer 5≤white hard carbon layer W]. Thus, the sp of the surface layer 5 composed of the white hard carbon layer is 2 / sp 3 The ratio is larger than that of the black hard carbon layer B and is about the same as that of the white hard carbon layer W. 2 / sp 3 The ratio is the same as that of the white hard carbon layer W (laminated portion 3) which has the same relative tone as when the cross section is observed using a bright field TEM image.
[0093] like Figure 6 and Figure 7 As shown, the surface portion 5 can be seen as a fine particle-like structure. The reason for this organizational morphology is not clear, but it is considered to be caused by the film forming conditions of the surface portion 5. In the surface portion 5, based on its film forming conditions, almost no hydrogen is contained. If the hydrogen content is to be expressed, it can be more than 0.01 atomic % and less than 5 atomic %. The hydrogen content can be measured by HFS (Hydrogen Forward Scattering: hydrogen forward scattering spectrometry) analysis, and the rest is preferably substantially composed of carbon and does not contain N, B, Si and other unavoidable impurities.
[0094] The range of Vickers hardness of the surface portion 5 and the white hard carbon layer W constituting the laminated portion 3 is significantly different. When the thickness of the surface portion 5 is set to be 0.1 μm or more and less than 1.0 μm, the Vickers hardness of the surface portion 5 is lower than the Vickers hardness of the white hard carbon layer W of the laminated portion 3, which is also a white hard carbon layer, and is within the range of 800 to 1200 HV. Moreover, this range (800 to 1200 HV) is about the same as the range (700 to 1600 HV) of the black hard carbon layer B of the laminated portion 3, but is a lower range. It should be noted that, as described above, when the thickness of the surface portion 5 is increased to 1 to 10 μm, the Vickers hardness of the surface portion 5 is lower than the Vickers hardness of the white hard carbon layer W of the laminated portion 3, which is also a white hard carbon layer, and is preferably a low hardness film within the range of 500 to 1000 HV, and more preferably within the range of 500 to 800 HV. It is considered that the surface layer portion 5 having such a Vickers hardness contributes to reducing friction when contacting with a counterpart member in the initial stage of sliding, functions as an affinity layer with the counterpart member, and achieves a function of preventing damage to the aluminum cylinder bore.
[0095] (Film formation of coating film)
[0096] The coating film 1 can be formed by a PVD method such as an arc PVD method and a sputtering PVD method. Among them, it is preferably formed by an arc ion plating method using a carbon target and containing no hydrogen atoms in the film-forming raw material. When the coating film 1 is formed by, for example, an arc ion plating method, ON / OFF of the bias voltage, control of the bias voltage value, adjustment of the arc current, heating control of the substrate by the heater, forced cooling of the substrate by introducing a cooling mechanism into the fixture (holder) where the substrate is set, etc. can be used as film forming conditions.
[0097] Specifically, in the film formation of the laminated portion 3, a high bias voltage is applied to the black hard carbon layer B to form the film, and a low bias voltage or no bias voltage is applied to the white hard carbon layer W to form the film. In the film formation of the carbon layer 4, the film formation of the laminated portion 3 is suspended for a certain period of time after the film formation, and the film is formed under specified conditions after reaching a lower temperature. In the film formation of the surface portion 5, the same or higher bias voltage as that of the aforementioned black hard carbon layer B is applied to form the film. Here, the "high" and "low" of the bias voltage refer to the absolute value. For example, taking -100V and -50V as examples, -100V is a higher bias voltage.
[0098] In the film formation of the stacked portion 3, sp 2 / sp 3The black hard carbon layer B with a ratio of 0.05 to 0.75 is formed at a bias voltage that causes a temperature rise. The bias voltage can be set, for example, in the range of -100 to -300 V, the arc current in this case is in the range of 40 to 120 A, and the substrate temperature is formed in the range of 100°C to 300°C. On the other hand, sp 2 / sp 3 The white hard carbon layer W with a ratio of 0.20 to 0.80 is formed at a bias voltage that does not cause a temperature rise. The bias voltage can be set to 0V or, for example, a range of 0V to -50V or less. At this time, the arc current is in the range of 40 to 120A, and the substrate temperature is not increased but gradually decreased to form a film. It should be noted that the substrate temperature can also be adjusted by adjusting the arc current, heater temperature, furnace pressure, etc. in addition to the bias voltage.
[0099] In the film formation of the carbon layer 4, a bias voltage higher than that of the black hard carbon layer B and the white hard carbon layer W constituting the laminated part 3 is applied to form the film. Specifically, the bias voltage is set to a range of -600 to -1000 V and the arc current is set to about 40 A to form the film. The carbon layer 4 is formed under such conditions because the film formation of the laminated part 3 is stopped for a certain period of time for the carbon layer 4, and the film is formed after reaching a relatively low temperature (for example, about 110°C). The certain period of rest is the time until the temperature becomes relatively low (for example, about 110°C).
[0100] The thickness of the surface layer 5 is preferably in the range of 0.1 to 10 μm. By making the thickness of the surface layer 5 thinner than 0.1 μm and less than 1.0 μm, it can have the effect of reducing friction when contacting with the other part in the initial stage of sliding. In addition, by making the thickness of the surface layer 5 thicker than 1 to 10 μm (more preferably 1 to 8 μm), it can have the effect of acting as an affinity layer with the other part and preventing damage to the aluminum cylinder bore. In the film formation of such a surface layer 5, a bias voltage equal to or higher than that of the aforementioned black hard carbon layer B is applied to form the film. If the bias voltage during the film formation of the black hard carbon layer B is, for example, -150 V, the bias voltage during the film formation of the surface layer 5 is set to a bias voltage higher than that (for example, -150 to -400 V, preferably -150 to -250 V). In the range of this bias voltage, the surface layer 5 can be formed in the same form (fine particle form) with no substantial difference. When forming the film under such a bias voltage, the film is formed at a temperature higher than the film forming temperature of each hard carbon layer (B, W) constituting the laminated portion 3 .
[0101] (sp 2 / sp 3 Compare)
[0102] The hard carbon layer is a carbon chain represented by graphite. 2 Chains and carbon chains represented by diamonds sp 3 In the present application, EELS analysis (Electron Energy-Loss Spectroscopy) was used to measure 1s→π * Intensity and 1s→σ * Intensity, 1s→π * Strength as sp 2 Intensity, 1s→σ * Strength as sp 3 intensity, and its ratio is 1s→π * Intensity and 1s→σ * The ratio of the intensity is given as [sp 2 / (sp 2 +sp 3 )] ratio (sometimes abbreviated as "sp 2 / sp 3 Therefore, the sp 2 / sp 3 Specifically, the spectral imaging method in STEM (scanning TEM) mode is used to analyze the sample with an acceleration voltage of 200 kV and a sample absorption current of 10 -9 A. The EELS obtained with a beam spot size of 1 nm in diameter and a pitch of 1 nm is integrated, and the C-K absorption spectrum is extracted as the average information from an area of about 10 nm to calculate sp 2 / sp 3 Compare.
[0103] Example
[0104] Hereinafter, the coating film and the sliding member according to the present invention will be described in further detail with reference to experimental examples and comparative experimental examples.
[0105] [Experimental Example 1]
[0106] A piston ring was used as the sliding member 10. A substrate 11 (diameter 88 mm, ring radial width 2.9 mm, ring axial width 1.2 mm) composed of C: 0.65 mass%, Si: 0.38 mass%, Mn: 0.35 mass%, Cr: 13.5 mass%, Mo: 0.3 mass%, P: 0.02 mass%, S: 0.02 mass%, and the rest: iron and inevitable impurities was used. On the substrate 11, a 40 μm nitride layer was formed as a base layer 12 by nitriding treatment, and a 0.2 μm thick metal chromium layer was formed as an intermediate layer 13 by ion plating. Next, on the intermediate layer 13, an initial carbon layer 14 with a thickness of 0.2 μm was formed by bombardment treatment (bias voltage: -750 V, arc current: 40 A). The laminated portion 3 was formed on the initial carbon layer 14. Regarding the laminated portion 3, an arc ion plating device using a carbon target was used to continuously form a laminated portion 3 with a thickness of about 5.3 μm by forming a repetitive unit 2 of 0.53 μm consisting of a black hard carbon layer B with a thickness of about 0.18 μm and a white hard carbon layer W with a thickness of about 0.35 μm 10 times. After that, after a rest period of about 135 minutes, a carbon layer 4 with a thickness of about 0.19 μm was formed using an arc ion plating device using the same carbon target. It should be noted that the substrate temperature dropped to about 110° C. after the rest period of about 135 minutes. After the formation of the carbon layer 4, the laminated portion 3 with a thickness of about 5.3 μm was formed again, and then the carbon layer 4 with a thickness of about 0.19 μm was formed again, and this operation was repeated. Finally, the laminated parts 3 were formed five times, the carbon layer 4 was formed between the laminated parts 3, and finally the surface layer 5 with a thickness of about 0.50 μm was formed on the laminated parts 3, forming a coating film 1 with a total thickness of about 27.8 μm.
[0107] Specifically, for the black hard carbon layer B constituting the laminated portion 3, arc discharge was performed for 10 minutes at a bias voltage of -150V and an arc current of 40A to form the film. For the white hard carbon layer W formed thereon, arc discharge (arc current 40A) was performed for 20 minutes at a bias voltage of -30V to form the film. For the carbon layer 4 formed between the laminated portions 3, arc discharge was performed for 22 minutes at a bias voltage of -750V and an arc current of 40A to form the film. For the surface layer 5, arc discharge was performed for 30 minutes at a bias voltage of -170V and an arc current of 40A to form the film.
[0108] [Observation of structural morphology]
[0109] A bright field TEM image of the cross section of the formed coating film 1 is taken. The cross-sectional image of the coating film 1 is obtained by taking a bright field TEM image of the cross section of the coating film 1 at an accelerating voltage of 200 kV. Figure 3 to Figure 5The TEM image of the coating film 1 obtained in Experimental Example 1 is shown in FIG. Figure 3 to Figure 5 As shown, it can be confirmed that for the laminated portion 3, the black hard carbon layer B which is relatively black and the white hard carbon layer W which is relatively white are alternately laminated in the thickness direction. In addition, fine stripe patterns can be seen in the white hard carbon layer W, and in the black hard carbon layer B, it seems that all or part of it has a mesh or fan-shaped structure. In addition, for the carbon layer 4, a black carbon layer 4a with a thickness of about 0.07μm and a white carbon layer 4b with a thickness of about 0.12μm can be seen, and in the white carbon layer 4b, a columnar structure 4c with relatively black columnar longitudinal ribs extending in the thickness direction can be seen. The surface layer 5 seems to have a fine particle-like structure.
[0110] The total thickness of the coating film 1, the thickness of each laminated portion 3, the thickness of each carbon layer 4, and the thickness of the surface layer portion 5 were obtained from the bright field TEM image. In the thickness measurement, a piston ring having the coating film 1 formed near the center of the effective coating range of the arc ion plating device used and a piston ring having the coating film 1 formed near the upper end and the lower end were used as the measurement samples. It should be noted that the ratio of the thickness TB of the black hard carbon layer B to the thickness TW of the white hard carbon layer W (TB / TW) is 0.18 / 0.35=0.51.
[0111] [Vickers hardness and sp 2 / sp 3 Compare]
[0112] Regarding Vickers hardness, the black hard carbon layer B has a Vickers hardness in the range of 700 to 1100 HV, and the white hard carbon layer W has a Vickers hardness in the range of 1200 to 1900 HV, which is higher than the Vickers hardness of the adjacent black hard carbon layer B. The Vickers hardness of the surface layer 5 is in the range of 900 to 1200 HV, which is lower than the Vickers hardness of the white hard carbon layer W of the laminated portion 3, which is also a white hard carbon layer.
[0113] It should be noted that, regarding the measurement of Vickers hardness, the thickness T (=TB+TW) of the repetition unit 2 of the experimental example 1 is 0.53 μm, the thickness of the black hard carbon layer B is 0.18 μm, the thickness of the white hard carbon layer W is 0.35 μm, and the thickness of the surface layer 5 is 0.50 μm, all of which are relatively thin, so the measurement of the hardness of each single layer is almost impossible even with the current highest level of measurement technology. In addition, even if it is to be measured from the surface, due to the thin thickness, it will be affected by the hardness of the lower layer, which is difficult even with the current highest level of measurement technology. Therefore, regarding the Vickers hardness here, the results of the measurement were evaluated by only forming the black hard carbon layer B, the white hard carbon layer W, and the surface layer 5 without changing the film forming conditions to make the layers thicker.
[0114] Specifically, the hardness is affected by the film forming temperature. Therefore, if the substrate temperature at the time when the film forming of the black hard carbon layer B is completed with the temperature rising is set as TempB, and the substrate temperature at the time when the film forming of the white hard carbon layer W is completed with the temperature falling is set as TempW, then TempB>TempW. In the case of forming a single layer of the black hard carbon layer B, after forming the black hard carbon layer B to a thickness of 0.18 μm, the substrate is cooled until the substrate temperature falls to TempW, and the film forming of the black hard carbon layer B is started at the time when TempW is reached, and the film forming of 0.18 μm is obtained. Thereafter, by repeating the cooling until the substrate temperature falls to TempW and the film forming of the black hard carbon layer B, a single layer film in which only the black hard carbon layer B is formed is obtained. On the other hand, in the case of forming a single layer of a white hard carbon layer W, after forming a 0.35 μm film of the white hard carbon layer W, the heater is heated until the substrate temperature rises to TempB, and the film formation of the white hard carbon layer W is started at the time point when TempB is reached, and the film formation of 0.35 μm is formed. Thereafter, by repeating the heating until the substrate temperature rises to TempB and the film formation of the white hard carbon layer W, a single layer film formed only on the white hard carbon layer W is obtained. In this way, in the measurement of the hardness from the surface, the single layer film of the black hard carbon layer B and the white hard carbon layer W formed to a film thickness (6 μm or more) not affected by the substrate is adjusted to a surface roughness of about Ra0.05, and the Vickers hardness is measured from the surface layer using a Vickers hardness tester with a load of 100 gf. In this experimental example, the Vickers hardness measured by this method is evaluated. The Vickers hardness of the surface layer 5 is also measured by the same means.
[0115] sp of the laminated part 3 2 / sp 3 The ratio is in the range of 0.05 to 0.55 in each part of the black hard carbon layer B, and in the range of 0.20 to 0.70 in each part of the white hard carbon layer W. 2 / sp 3 The ratio is in the range of 0.20 to 0.60 in each part. 2 / sp 3 The ratio is in the range of 0.40 to 0.55 in each part of the surface layer 5. It should be noted that the black hard carbon layer B, the white hard carbon layer W, the white carbon layer 4b and the sp 2 / sp 3 The ratio is the result of measurement at each part. However, the value at the interface with other layers may change due to the influence of other layers. Therefore, avoid using the interface with other layers as the measurement point.
[0116] [Abrasion resistance, chipping resistance, low friction, peeling resistance]
[0117] The various properties of the coating film 1 after film formation were obtained by a friction and wear test method based on an SRV (Schwingungs Reihung und Verschleiss) tester 120, which is generally performed in the evaluation of sliding parts for automobiles. Fig. 9 As shown, the sliding surface of the friction and wear test sample 20 was brought into contact with the SUJ2 material as the sliding object 21, and the lubricant was 5W-30 (with Mo-DTC). A load of 1000N was applied while the sample was reciprocated for 10 minutes and 60 minutes, and the sliding surface of the friction and wear test sample 20 was observed under a microscope. Fig. 9 In the figure, reference numeral 12 is an intermediate layer, and reference numeral 1 is a coating film.
[0118] The obtained coating film 1 was confirmed to have constant and stable chipping resistance and abrasion resistance and excellent peeling resistance (adhesion). Furthermore, it was confirmed that even corners (also called edge portions) where stress is particularly likely to accumulate, no chipping or cracking occurred.
[0119] As described above, the coating 1 obtained in Experimental Example 1 has good resistance to chipping and wear, and low aggressiveness to the other material, so it has stable sliding characteristics for both the coating 1 and the other material. In particular, due to the effect of the carbon layer 4 set between the laminated parts, even the corners (also called edge parts) where stress is easily accumulated do not produce defects or cracks. In addition, the cross-sectional morphology of each laminated part 3 appearing in the thickness direction Y of the coating 1 is homogeneous, so it can be considered that the characteristics in the thickness direction Y are also homogeneous, and both homogenization and thickening can be achieved with high productivity. In addition, such a feature is particularly ideal for sliding parts and coatings that are subjected to high loads, such as piston rings, and can become a sliding part with constant and stable characteristics compared to sliding parts that do not have this feature. In addition, since the coating 1 has a surface layer 5 on the outermost surface, it is possible to reduce the friction when contacting with the other part in the initial stage of sliding.
[0120] [Experimental Example 2]
[0121] This Experimental Example 2 also uses a piston ring as a sliding member 10, uses the same substrate 11 as in Experimental Example 1, and forms the nitride layer, the intermediate layer 13, and the initial carbon layer 14 as the base layer 12 in the same manner as in Experimental Example 1. The repetitive unit 2 of the black hard carbon layer B and the white hard carbon layer W is also formed in the same manner as in Experimental Example 1 to form a plurality of laminated portions 3 of a predetermined thickness, and forms a carbon layer 4 between the plurality of laminated portions 3, and finally forms a surface layer 5, thereby obtaining a coating film 1.
[0122] In Experimental Example 2, the film forming conditions (bias voltage, arc current, film forming time) were not changed but the film forming thickness was changed. Specifically, the thickness of the repetitive unit 2 composed of the black hard carbon layer B and the white hard carbon layer W was the same as that in Experimental Example 1, but for the laminated portion 3, the film forming of the repetitive unit 2 was repeated 17 times to form a laminated portion 3 with a thickness of 9 μm, and the laminated portion 3 was formed 3 times. The carbon layer 4 was formed with a thickness of 0.1 μm between each laminated portion 3. The surface layer 5 was the same as Experimental Example 1. The thickness of the coating film 1 was 27.7 μm. It should be noted that for the carbon layer 4, a black carbon layer 4a with a thickness of about 0.05 μm and a white carbon layer 4b with a thickness of about 0.05 μm were formed, and a columnar structure 4c with relatively black columnar longitudinal ribs extending in the thickness direction can be seen in the white carbon layer 4b.
[0123] [Evaluation of Experimental Example 2]
[0124] The evaluation of various characteristics and the like was the same as the above method. For the coating film 1 of Experimental Example 2, the bright field TEM image of its cross section showed that the only difference was the thickness ratio of the black carbon layer 4a and the white carbon layer 4b constituting the carbon layer 4. Figure 3 to Figure 5 Same form.
[0125] sp of the laminated part 3 2 / sp 3 The ratio is in the range of 0.05 to 0.55 in each part of the black hard carbon layer B, and in the range of 0.20 to 0.70 in each part of the white hard carbon layer W. 2 / sp 3 The ratio is in the range of 0.20 to 0.60 in each part. 2 / sp 3 The ratio is in the range of 0.40 to 0.55.
[0126] The obtained coating film 1 was confirmed to have constant and stable chipping resistance and abrasion resistance and excellent peeling resistance (adhesion). Furthermore, it was confirmed that even corners (also called edge portions) where stress is particularly likely to accumulate, no chipping or cracking occurred.
[0127] [Experimental Example 3]
[0128] In Experimental Example 3, a piston ring was also used as the sliding member 10, and the same substrate 11 as in Experimental Example 1 was used, and the nitride layer, the intermediate layer 13, and the initial carbon layer 14 as the base layer 12 were also formed in the same manner as in Experimental Example 1. For the repetitive unit 2 of the black hard carbon layer B and the white hard carbon layer W, a plurality of laminated portions 3 of a predetermined thickness were formed in the same manner as in Experimental Example 1, a carbon layer 4 was formed between the plurality of laminated portions 3, and finally a surface layer 5 was formed to obtain a coating film 1.
[0129] In this Experimental Example 3, the film forming conditions (bias voltage, arc current, film forming time) are not changed but the film forming thickness is changed. Specifically, the thickness of the repetitive unit 2 composed of the black hard carbon layer B and the white hard carbon layer W is the same as that in Experimental Example 1, but for the laminated portion 3, the film forming of the repetitive unit 2 is repeated 10 times to form a laminated portion 3 with a thickness of 5.3 μm, and the laminated portion 3 is formed twice. The carbon layer 4 is formed with a thickness of 0.19 μm between each laminated portion 3. For the surface layer 5, it is the same as in Experimental Example 1. The thickness of the coating film 1 is 11.3 μm. It should be noted that for the carbon layer 4, a black carbon layer 4a with a thickness of about 0.07 μm and a white carbon layer 4b with a thickness of about 0.12 μm are formed, and a columnar structure 4c with relatively black columnar longitudinal ribs extending in the thickness direction can be seen in the white carbon layer 4b.
[0130] [Evaluation of Experimental Example 3]
[0131] The evaluation of various characteristics and the like was the same as the above method. For the coating film 1 of Experimental Example 3, the bright field TEM image of its cross section showed a difference in thickness ratio between the black carbon layer 4a and the white carbon layer 4b constituting the carbon layer 4. Figure 3 to Figure 5 Same form.
[0132] sp of the laminated part 3 2 / sp 3 The ratio is in the range of 0.05 to 0.55 in each part of the black hard carbon layer B, and in the range of 0.20 to 0.70 in each part of the white hard carbon layer W. 2 / sp 3 The ratio is in the range of 0.20 to 0.60 in each part. 2 / sp 3 The ratio is in the range of 0.40 to 0.55.
[0133] The obtained coating film 1 was confirmed to have constant and stable chipping resistance and abrasion resistance and excellent peeling resistance (adhesion). Furthermore, it was confirmed that even corners (also called edge portions) where stress is particularly likely to accumulate, no chipping or cracking occurred.
[0134] [Experimental Example 4]
[0135] In Experimental Example 4, the thickness of the surface layer 5 (0.50 μm) in Experimental Example 1 was increased to 7 μm by extending the film forming time. The coating film 1 of Experimental Example 4 having a total thickness of 34.3 μm was formed in the same manner as in Example 1. The obtained coating film 1 was confirmed to have an improved effect of the affinity layer and the damage prevention effect with respect to the counterpart member, i.e., the aluminum cylinder bore, because the surface layer 5 was thickened.
[0136] [Comparative Experiment Example 1]
[0137] In this comparative experimental example 1, a piston ring was used as a sliding member 10, and the same substrate 11 as in the experimental example 1 was used. The nitride layer, the intermediate layer 13, and the initial carbon layer 14 as the base layer 12 were also formed in the same manner as in the experimental example 1. The film formation was performed in the same manner as in the experimental example 1 for the repetitive unit 2 of the black hard carbon layer B and the white hard carbon layer W, but the film formation of the repetitive unit 2 was repeated 20 times, and finally the surface layer 5 was formed to obtain a coating film 1 with a total thickness of 11.1 μm. In this comparative experimental example 1, a plurality of laminated parts were formed as in the experimental example 3, but the carbon layer 4 was not formed between the laminated parts 3. It should be noted that the film formation conditions of the black hard carbon layer B, the white hard carbon layer W, and the surface layer 5 were the same as in the experimental example 1.
[0138] [Evaluation of Comparative Experimental Example 1]
[0139] Evaluation of various properties and the like was performed in the same manner as described above. In the obtained coating film 1, portions where slight chipping and cracking occurred were observed at corner portions (also referred to as edge portions) where stress easily accumulates.
[0140] [Comparative Experiment Example 2]
[0141] In this comparative experimental example 2, a piston ring was used as a sliding member 10, and the same substrate 11 as in the experimental example 1 was used. The nitride layer, the intermediate layer 13, and the initial carbon layer 14 as the base layer 12 were also formed in the same manner as in the experimental example 1. The film formation of the repetitive unit 2 of the black hard carbon layer B and the white hard carbon layer W was performed in the same manner as in the experimental example 1, but the film formation of the repetitive unit 2 was repeated 50 times, and finally the surface layer 5 was formed to obtain a coating film 1 with a total thickness of 27.0 μm. In this comparative experimental example 2, a plurality of laminated parts were formed as in the experimental example 1, but the carbon layer 4 was not formed between the laminated parts 3. It should be noted that the film formation conditions of the black hard carbon layer B, the white hard carbon layer W, and the surface layer 5 were the same as in the experimental example 1.
[0142] [Evaluation of Comparative Experimental Example 2]
[0143] Evaluation of various characteristics and the like was performed in the same manner as described above. In the obtained coating film 1, slightly more defects and cracks were observed than in Comparative Experimental Example 1 at corners (also referred to as edges) where stress is easily accumulated.
[0144] As mentioned above, although this invention was demonstrated based on embodiment, this invention is not limited to said embodiment. Various changes can be implemented to said embodiment within the range which is the same as this invention and is equivalent.
[0145] Description of Reference Numerals
[0146] 1. Coating film;
[0147] 2 repeated units;
[0148] 3. Lamination section;
[0149] 4. Carbon layer between laminated parts (carbon layer between laminated parts);
[0150] 4a Black carbon layer;
[0151] 4b white carbon layer;
[0152] 4c columnar organization;
[0153] 5 superficial part;
[0154] 10 sliding parts (piston rings);
[0155] 11 base material (piston ring base material);
[0156] 12 basal layer;
[0157] 13 middle layer;
[0158] 14 Carbon layer formed by bombardment (initial carbon layer);
[0159] 15 thin carbon layer (carbon layer inside the laminate);
[0160] 16 sliding surface;
[0161] 20 Friction and wear test specimens;
[0162] 21 Sliding objects;
[0163] 120SRV test machine;
[0164] B Black hard carbon layer;
[0165] W white hard carbon layer;
[0166] Y thickness direction;
[0167] X is the in-plane direction;
[0168] TB is the thickness of the black hard carbon layer;
[0169] TW is the thickness of the white hard carbon layer;
[0170] T1 coating film thickness;
[0171] T2 is the thickness of the repeated unit;
[0172] T3 thickness of the laminated portion;
[0173] T4 Carbon layer thickness.
Claims
1. A sliding component having a coating film on a sliding surface on a substrate, characterized in that: The coating film has a plurality of stacked parts and a carbon layer arranged between each of the stacked parts. For the stacked parts, when a cross section is observed using a bright field TEM image, repeated units of a hard carbon layer that appears relatively black or blackish and a hard carbon layer that appears relatively white or whiteish are stacked in the thickness direction, and the carbon layer has a columnar structure.
2. The sliding component according to claim 1, The thickness of the laminated portion is in the range of 2 to 9 μm, and the thickness of the coating film is in the range of 4 to 40 μm.
3. The sliding component according to claim 1 or 2, The carbon layer includes a black carbon layer that is relatively black or skewed black and a white carbon layer that is relatively white or skewed white in sequence, and the columnar structure that is relatively black or skewed black exists in the white carbon layer.
4. The sliding member according to claim 3, The black hard carbon layer 2 / (sp 2 +sp 3 )] ratio is in the range of 0.05 to 0.75, and the white hard carbon layer has a [sp 2 / (sp 2 +sp 3 )] is greater than the [sp 2 / (sp 2 +sp 3 )] ratio and is in the range of 0.20 to 0.80, the white carbon layer in the carbon layer has a [sp 2 / (sp 2 +sp 3 )] ratio is in the range of 0.20 to 0.
80.
5. The sliding component according to claim 1 or 2, An initial carbon layer is formed as a lower layer before the coating film is formed.
6. The sliding component according to claim 1 or 2, In the laminated portion, an inner-laminated portion carbon layer is formed on the white hard carbon layer as a lower layer of the black hard carbon layer.
7. The sliding component according to claim 1 or 2, The laminated portion has a surface layer portion as an outermost layer, and the thickness of the surface layer portion is 0.1 to 10 μm.
8. The sliding component according to claim 1 or 2, The sliding member is a piston ring.
9. A coating film, characterized in that: The invention has a plurality of stacked parts and a carbon layer arranged between each of the stacked parts. For the stacked parts, when a cross section is observed using a bright field TEM image, repeated units of a hard carbon layer that is relatively black or blackish and a hard carbon layer that is relatively white or whiteish are stacked in the thickness direction, and the carbon layer has a columnar structure.
10. The coating film according to claim 9, The thickness of the laminated portion is in the range of 2 to 9 μm, and the thickness of the coating film is in the range of 4 to 40 μm.
11. The coating film according to claim 9 or 10, The carbon layer includes a black carbon layer that is relatively black or skewed black and a white carbon layer that is relatively white or skewed white in sequence, and the columnar structure that is relatively black or skewed black exists in the white carbon layer.
12. The coating film according to claim 9 or 10, An initial carbon layer is formed as a lower layer before the coating film is formed.
13. The coating film according to claim 9 or 10, In the laminated portion, an inner-laminated portion carbon layer is formed on the white hard carbon layer as a lower layer of the black hard carbon layer.
14. The coating film according to claim 9 or 10, The laminated portion has a surface layer portion as an outermost layer, and the thickness of the surface layer portion is 0.1 to 10 μm.
15. A method for manufacturing a sliding component, the method for manufacturing a sliding component according to claim 1 or 2, wherein the sliding surface of the substrate has a coating film, wherein: The coating film has a plurality of laminated parts and a carbon layer provided between the laminated parts, wherein the laminated parts have repeated units of a relatively black or blackish hard carbon layer and a relatively white or whiteish hard carbon layer laminated in a thickness direction when a cross section is observed using a bright field TEM image, and the carbon layer has a columnar structure. The carbon layer is obtained by forming the laminated portion to a predetermined thickness, pausing the film formation for a predetermined period of time, and then forming the film under predetermined conditions after the temperature reaches a relatively low level.
Citation Information
Patent Citations
Sliding member and coating film
WO2018235750A1